MENSTRUAL DISORDER AND QUALITY OF LIFE AMONG FEMALE COLLEGE ADOLESCENTS IN SELANGOR - Faieza Samat; Nurul Atiqah Mohamad Azam G; Amalina Alya Azizan; Nur Azurah Abdul Ghani (Asian Journal of Medicine & Health Sciences, 2020)
Background: Menstrual disorder is a womanhood problem around the world and negatively affects the quality of life. In females, common menstrual disorders are dysmenorrhoea, oligomenorrhoea and menorrhagia. Methodology: A cross-sectional study was carried out among 294 female college adolescents aged 18 to 20 years in UKM, UM and UiTM. A set of questionnaires on demography, menstrual patterns and health-related quality of life was distributed online over a period of about 10 days in December 2019. Results: A total of 294 questionnaires were analysed. The mean age of the participants was 18.36±0.64 years with a range of 18 to 20 years. Of all participants, 53% had dysmenorrhoea ranging from moderate to very severe while 16% had menorrhagia while 10% had oligomenorrhoea. Quality of life in females with menstrual disorders were poor (43.56 ± 6.31) compared to the normal females (46.67 ± 5.58) in physical and mental health with p-value <0.001. Conclusion: This study found that dysmenorrhoea is most prevalent menstrual disorder in female college students aged 18 to 20 years. Furthermore, the quality of life in females with menstrual disorders were poor both physically and mentally.